Dangerous creatures - Garcia, Kami; Stohl, Margaret (Garcia, Kami. Dangerous creatures., 2014)
"Siren Ridley and her rocker boyfriend Link move to New York City to make it big with their supernatural band mates in Sirensong, but Caster trouble follows them"--